Analysis of the Influence of Compensation, Motivation and Job Satisfaction on Employee Performance at PT Ira Widya Utama - Nicco Ramadannu; Hasrul Hasibuan (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the influence of compensation, motivation, and job satisfaction on employee performance at PT. Ira Widya Utama. Primary data was obtained through interviews and the distribution of questionnaires to 50 employees which were then analyzed using statistical tools. The data collection techniques used include direct interviews and questionnaires to obtain respondents' responses regarding factors affecting performance. This study also uses validity and reliability tests to ensure that the research instrument is feasible to use. The results showed that compensation had a positive and significant influence on employee performance, with a calculated t value of 3.933 which was greater than the table t of 1.675 and a significance value of 0.000. This shows that employees who receive good compensation tend to have better performance. Work motivation had a significant effect on employee performance, with a t-value of 2.071 which was greater than the t-table of 1.675 and a significance value of 0.041. This shows that work motivation plays an important role in improving performance. Job satisfaction was proven to have a positive and significant influence on employee performance, with a t-value of 4.960 and a significance value of 0.000, indicating that employees who were satisfied with their jobs were more committed and made maximum contributions. Simultaneously, all three independent variables—compensation, motivation, and job satisfaction—had a positive and significant influence on employee performance, with an F value of 93.650 which was greater than the F table of 2.366 and a significance value of 0.000. This study confirms that the combination of these three variables can improve employee performance optimally.